Promoting multicultural speaking and listening activities to improve student diversity awareness - Floriasti, Tri Wahyuni; Sudiyono, Sudiyono (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2022)
This study seeks to improve pre-service teachers' cross-cultural communication abilities and cultural awareness through intercultural speaking and listening exercises. In light of our interconnected world, encouraging successful cross-cultural dialogue is crucial. Getting through language obstacles, different communication styles, and cultural variations is the difficult part. Action research in the classroom is used in the study. Twenty first-year pre-service teachers from the English Education Department make up the participants, who participate in successive exercises to foster intercultural competency. Observations, reflective journals, and post-activity talks are ways to collect data. The results show that over the three cycles, participants' multicultural speaking and listening abilities, cultural sensitivity, and cross-cultural communication proficiency all improved. Participants in Cycle 1 showed a 15% increase in participation and openness to talking about cultural issues. Cycle 2 saw more complex dialogues and a 25% deeper understanding of culture. By Cycle 3, participants had exhibited significant cultural empathy and 40% flawless communication. The study's success highlights the mutually beneficial interaction between theoretical underpinnings and actual application. Embracing constructivist methodology, encouraging reflective practices, giving varied cultural scenarios, facilitating collaborative learning spaces, utilizing technology, and creating opportunities for professional growth are just a few suggestions. Other suggestions include integrating multicultural activities. This study exemplifies the transforming power of fusing theory and practice in developing the next generation of educators into skilled intercultural communicators and global citizens.